The Impact of Customer Engagement on Brand Loyalty: The Mediation Roles of Brand Attachment and Customer Trust - Azizah Chairunnisa; Endang Ruswanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explores the influence of brand love and brand experience on customer engagement and then the influence of customer engagement on brand loyalty directly or mediated by brand attachment and customer trust in cosmetic industry brands in Indonesia. This research was conducted in 2022 by involving 202 respondents using Instagram who is women of the millennial generation in Indonesia. Quantitative research using the Structural Equation Model (SEM) method with data analysis using SmartPLS. Some of the findings in this study are that brand love and brand experience indirectly affect brand loyalty mediated by brand attachment and customer trust. Meanwhile, customer engagement does not have a direct influence on increasing brand loyalty directly. The managerial implications of this research for industry practitioners and researchers are to build strong brand love, and brand experience will be able to create customer engagement, then loyalty to the customer's brand will be higher when the brand can strengthen customer engagement which then creates brand attachment and customer trust